2019
DOI: 10.1002/cncr.32489
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbance and neurocognitive outcomes in older patients with breast cancer: Interaction with genotype

Abstract: Background Sleep disturbance and genetic profile are risks for cognitive decline in noncancer populations, yet their role in cancer‐related cognitive problems remains understudied. This study examined whether sleep disturbance was associated with worse neurocognitive outcomes in breast cancer survivors and whether sleep effects on cognition varied by genotype. Methods Newly diagnosed female patients (n = 319) who were 60 years old or older and had stage 0 to III breast cancer were recruited from August 2010 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
3
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 54 publications
(124 reference statements)
5
40
3
3
Order By: Relevance
“…Other common cancer-related symptoms are also important factors associated with cognitive dysfunction. In this study, anxiety and fatigue were related to subjective cognitive dysfunction; but in contrast to previous studies sleep disturbance was not significantly correlated [17,47]. Although somewhat inconsistent in the literature, other cancer-related symptoms such as anxiety, fatigue, and sleep disturbance have been shown to be significantly correlated with perceived cognitive dysfunction either as independent symptoms or as a cluster of symptoms (identified as the psychoneurological symptom cluster) and these relationships have been noted in all age BCS [43,48] as well as older BCS [13,14,16,47,49].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Other common cancer-related symptoms are also important factors associated with cognitive dysfunction. In this study, anxiety and fatigue were related to subjective cognitive dysfunction; but in contrast to previous studies sleep disturbance was not significantly correlated [17,47]. Although somewhat inconsistent in the literature, other cancer-related symptoms such as anxiety, fatigue, and sleep disturbance have been shown to be significantly correlated with perceived cognitive dysfunction either as independent symptoms or as a cluster of symptoms (identified as the psychoneurological symptom cluster) and these relationships have been noted in all age BCS [43,48] as well as older BCS [13,14,16,47,49].…”
Section: Discussioncontrasting
confidence: 99%
“…Demographic (age and education), medical (comorbidities), and disease factors (time since diagnosis and breast cancer stage) have been shown to be significantly related to cognitive dysfunction [3,[13][14][15]. In addition, other cancer-related symptoms, including depressive symptoms, anxiety, fatigue, and sleep disturbance have been previously linked with cognitive dysfunction [13,14,[16][17][18]. However, in all age BCS and the smaller volume of literature focusing on older BCS, these findings have been mixed [19].…”
Section: Introductionmentioning
confidence: 99%
“…Our result that the APOE ε2 allele may confer protection against cognitive decline for cancer survivors selected to receive chemotherapy adds a new dimension to the body of evidence supporting a role of APOE genotype broadly and strengthens evidence suggesting parallels between CRCD and AD ( 9 , 12 , 15 , 31 , 53 ). This idea is supported by indirect evidence, including neuroimaging studies showing that breast cancer survivors and individuals with AD have abnormalities in similar brain regions ( 54 , 55 ) and overlap in the cognitive domains affected ( 9 , 56 ).…”
Section: Discussionsupporting
confidence: 78%
“…Other clinically relevant findings include the fact that similar to past studies of CRCD ( 15 ) and current models of dementia risk ( 50 ), we found that APOE genotypes do not correspond to a family history of dementia. Further, baseline mood symptoms and smoking history failed to explain the relationship between ε2 status and neuropsychological outcomes, suggesting these are distinct clinical outcomes, consistent with current multifactorial theories of CRCD ( 3 , 6 , 31 ).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation